Indonesian Hip-Hop Battle for Autonomy - Aryandari, Citra (Institut Seni Indonesia Denpasar, 2024)
Purpose: This study will discuss how hip-hop music in Indonesia struggles to find a place amid the onslaught of the world's massive pop music industry and the regional pop music industry. Research method: By using qualitative methods, as well as data collection techniques carried out through the process of observation, interviews, and literature study. This research provides an overview of how Indonesian Hip Hop with idealism can create its market and how the Hip Hop community in Indonesia makes a living on its autonomy. Results and discussion: Hip-hop was initially born as a subculture that tried to fight the practice of racism against black people with the spirit of resistance. Hip-hop then grew into a music genre to respond to political issues and portray the social realism of society. The development of Hip Hop has also spread to various countries globally, including Indonesia. Hip Hop then become part of the global music industry and is entering a golden age. Implication: The hip-hop music industry is slowly experiencing its twilight period after the birth of mainstream music hegemony. The independent music scene has become a counterculture to the supremacy of mainstream music. Independent musicians with a do-it-yourself spirit ethos have succeeded in creating their ecosystem.